Competition for Flexible Distribution Resources in a 'Smart' Electricity Distribution Network - Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2020)
In a 'smart' electricity distribution network, flexible distribution resources (FDRs) can be coordinated to improve efficiency. But coordination enables whoever controls such resources to exercise market power. The paper establishes the following efficiency rankings of market structures: Aggregators competing for FDRs are more efficient than a distribution system operator (DSO) controlling resources, which is more efficient than no FDR market. A no- market solution is more efficient than an FDR market featuring either (i) both DSO and aggregators; or (ii) a monopoly aggregator also supplying generation to the real-time market. The paper also characterizes a regulation that implements the efficient outcome.
Keywords: H41; L12; L51; L94; 330; Aggregator; Distribution system operator; Market power; Real-time market; Regulation; Smart grid